Heaven official's blessing : the comic 1= Tian guan ci fu - Moxiangtongxiu; STARember (Inklore, 2025)
"Xie Lian, once the darling of the heavens, is a twice-banished god infamous for his fall from grace. Eight hundred years have passedsince his mortal life as the Crown Prince of Xianle, and he?s now the laughingstock of the three realms. So when he ascends to godhood for a third time, it causes an uproar among his divine peers. Ascension may be nothing new to Xie Lian, but this time he has no followers, little power, and less luck. To repay his heavenly debts, Xie Lian must descend to the Mortal Realm to hunt ghosts that prey upon theliving. There, he encounters a mysterious stranger--but is this newcomer friend or foe..or so mething else entirely?"--Provided by publisher.